2003
DOI: 10.1021/ol036157o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Protection of Aryl Sulfates Using the 2,2,2-Trichloroethyl Moiety

Abstract: [reaction: see text] The 2,2,2-trichloroethyl (TCE) group was utilized as the first protecting group for aryl sulfates. Aryl sulfates, protected with the TCE group, were prepared in high yield by reacting phenols with chlorosulfuric acid TCE ester. Deprotection was accomplished using Pd/C-ammonium formate or with Zn-ammonium formate to give aryl sulfate monoesters in high yield. This approach to aryl sulfate synthesis was successfully applied to the construction of estrone sulfate derivatives, which could not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
71
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 22 publications
0
71
0
Order By: Relevance
“…Several years ago we suggested that estrone sulfate (E1S) derivatives 1-4 could potentially act as suicide inhibitors of STS. [2] Hydrolysis of the SÀO bonds in 1-4 by STS would produce quinone methides in the active site that could react with residues required for catalysis, thus inactivating STS (as illustrated for compound 1 in Scheme 2). Herein we show that several of these compounds are suicide inhibitors of STS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several years ago we suggested that estrone sulfate (E1S) derivatives 1-4 could potentially act as suicide inhibitors of STS. [2] Hydrolysis of the SÀO bonds in 1-4 by STS would produce quinone methides in the active site that could react with residues required for catalysis, thus inactivating STS (as illustrated for compound 1 in Scheme 2). Herein we show that several of these compounds are suicide inhibitors of STS.…”
mentioning
confidence: 99%
“…[2] Compounds 3 and 4 were prepared by using a similar approach (Scheme 3). [3] A trichloroethyl-protected sulfate group was introduced onto 4-formyl estrone (4-FE1) [4] by using trichloroethylsulfuryl chloride [2] to give compound 5.…”
mentioning
confidence: 99%
“…[5] Recently, we described the use of the 2,2,2-trichloroethyl (TCE) group as the first protecting group developed for aryl sulfates. [6] The TCE-protected sulfate esters were prepared in a single step by the reaction of phenols with 2,2,2-trichloroethyl chlorosulfate (TCECS) in the presence of triethylamine. The resulting protected sulfates were stable to a variety of conditions, but were readily deprotected in excellent yields under neutral conditions with Pd/C-ammonium formate or zinc-ammonium formate.…”
Section: Introduction Of 222-trichloroethyl-protectedmentioning
confidence: 99%
“…5,6 For the structure-activity relationship studies concerning integrase inhibition and anti-HIV activity, we needed to prepare lamellarin 13-sulfate (2) and 13,20-disulfate (4) also. It was revealed, however, the synthesis of 2 from 5 was difficult because debenzylation at 20-OBn occurred simultaneously during deprotection at 13-Oi-Pr under the standard BCl 3 conditions.…”
mentioning
confidence: 99%
“…Thus, we designed a new lamellarin derivative (6) in which 13-OH was protected by a more labile methoxymethyl (MOM) group. In this communication, we report a divergent synthesis of lamellarin sulfate derivatives (1), (2), and (4) from the common intermediate (6) which in turn can be obtained from 3,4-dihydroxypyrrole bistriflate (7) and arylboronic acids (8), (9) using the previously established procedure developed in our laboratories (Scheme 1). …”
mentioning
confidence: 99%